Car of configuration turn blind area safety detection system - CHEN HUA (2018)
The utility model relates to a car of configuration turn blind area safety detection system, it includes the vapour driving license body, on -vehicle computer, car A post safety detection device, carA post safety detection device and on -vehicle computer constitute the control electricity and connect, car A post safety detection device is fixed to be set up on the A post of the vapour driving license body, and car A post safety detection device includes detecting device and LED lamp strip, and fixed A post of locating the vapour driving license body of LED lamp strip is inboard, and detectingdevice is fixed to be set up outside the A post of the vapour driving license body, and detecting device and LED lamp strip constitute the control electricity with on -vehicle computer and be connected, detecting device includes that camera, sound radar and infrared ray constitute the data electricity apart from detecting head and on -vehicle computer and are connected apart from detecting head,camera, sound radar and inf